2015
DOI: 10.1111/cyt.12283
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing the results of the invasive cervical cancer review to patients: a survey of lead colposcopists across England

Abstract: Despite National Health Service Cervical Screening Programme guidelines, not all clinicians offer review meetings to patients and those who do offer them do not always offer them to all women. Patient research needs to be conducted to explore the value of the meetings further, and there is a need to do more to engage clinicians in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Sherman et al surveyed lead colposcopists regarding disclosing the results of invasive cervical cancer reviews to patients in 2015. 12 This study preceded Duty of Candour legislation but followed the introduction of an open disclosure policy. The authors found that despite NHS Cervical Screening Programme guidelines only 53% of all responding clinicians offered review meetings to patients and those that did offer meetings did not offer to all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sherman et al surveyed lead colposcopists regarding disclosing the results of invasive cervical cancer reviews to patients in 2015. 12 This study preceded Duty of Candour legislation but followed the introduction of an open disclosure policy. The authors found that despite NHS Cervical Screening Programme guidelines only 53% of all responding clinicians offered review meetings to patients and those that did offer meetings did not offer to all patients.…”
Section: Discussionmentioning
confidence: 99%